BOOSTING INDONESIA’S DIGITAL COMPETITIVENESS: INSIGHTS FROM THE 2023 EAST VENTURES INDEX - Hilda (Acta Informatica Malaysia)
This research aims to analyze and provide an understanding of Indonesia’s digital competitiveness in an increasingly competitive digital era. This research uses a quantitative descriptive method by utilizing secondary data from the 2023 East Ventures-Digital Competitiveness Index (EV-DCI). The main finding of this research is that Indonesia has experienced an increase in digital competitiveness, marked by an increase in the EV-DCI score from the previous year. However, there are still challenges that need to be overcome, such as limited digital infrastructure, gaps in digital access and skills, and expanding regulations that support digital innovation. The main contribution of this research is to provide insight into the actual situation of Indonesia’s digital competitiveness and provide a basis for developing more effective strategies for increasing competitiveness in this digital era.